2010
DOI: 10.1097/tp.0b013e3181ca7e9b
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Utility of Deceased Donor Implantation Biopsy in Determining Function and Graft Survival After Kidney Transplantation

Abstract: Therefore, although biopsy evidences of vascular pathologic condition, kidney may contribute meaningfully to the assessment of donor quality but the degree of GS does not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 42 publications
3
60
1
2
Order By: Relevance
“…Though in many cases renal biopsy at the time of recovery assumes critical importance in discriminating for acceptance of suboptimal donors [24,25], this procedure holds some disadvantages to be taken into account, primarily the lengthening of transplant procedure time and the exposure of the organ to bleeding risk especially in the presence of chronic organ degeneration. For this reason we sought to establish ex-post if the application of Nyberg’s clinical score had disclosed substantial differences in terms of organ allocation and transplant outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Though in many cases renal biopsy at the time of recovery assumes critical importance in discriminating for acceptance of suboptimal donors [24,25], this procedure holds some disadvantages to be taken into account, primarily the lengthening of transplant procedure time and the exposure of the organ to bleeding risk especially in the presence of chronic organ degeneration. For this reason we sought to establish ex-post if the application of Nyberg’s clinical score had disclosed substantial differences in terms of organ allocation and transplant outcome.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, the study by Kahu et al clearly shows that more advanced histologic lesions have a greater impact on graft survival in grafts from donors with four or more risk factors than in those from donors with three or fewer risk factors. Questions remain, however, regarding the applic ability of their findings in the clinical setting.…”
Section: Edmund Huang Gabriel Danovitch and Suphamai Bunnapradistmentioning
confidence: 96%
“…Other parameters, such as vascular lesions, may be more predictive of graft survival than is glomerulosclerosis. 8 The CADI score utilized by Kahu and colleagues incorporates multiple histologic parameters and associates with graft survival in grafts with a higher donor risk score (>3), but not in those with a donor score of ≤3.…”
Section: Edmund Huang Gabriel Danovitch and Suphamai Bunnapradistmentioning
confidence: 99%
“…19 Most investigators agree that glomerulosclerosis alone is limited in its overall predictive value. 20 Other studies have emphasized donor vascular disease as the most important histologic predictor of graft function, 20 but evaluation of vessels may be affected by biopsy technique. Some studies have shown that wedge biopsies underestimate the amount of arterial sclerosis compared with core biopsies.…”
Section: Preimplantation Donor Biopsy Evaluationmentioning
confidence: 99%